Efektivitas Penerapan Model Pasa dalam Pembelajaran Daring untuk Meningkatkan Minat Belajar dan Hasil Belajar Sosiologi - Christiningsih, Grace Nadia; Trinugraha, Yosafat Hermawan; Rahman, Abdul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to analyze whether the application of the Picture and Student Active (PASA) model in online learning is effective in increasing interest and learning outcomes in Sociology in SMA Batik 1 Surakarta class X-IPS during the 2021/2022 academic year. The research method used was a quasi-experimental method with the Contextual Teaching and Learning (CTL) approach, a sample of 99 students was taken randomly, the data were obtained from distributing questionnaires and analyzed using descriptive statistical analysis. The results in this study indicate that there are differences in students' learning interests before and after the application of the PASA model in Sociology lessons, there are differences in student learning outcomes before and after the application of the PASA learning model in Sociology subjects, there is a greater increase in student learning outcomes students who apply the PASA learning model, and there is a greater increase in learning outcomes for students who apply the PASA model. Based on these results, the school is expected to provide support to teachers in providing subject matter using interesting and varied learning models such as the PASA model so that student interest and learning outcomes increase. For teachers, it is suggested that there are more alternatives in terms of increasing students' interest in the learning process by applying the PASA learning model. Keywords: Learning Outcomes, Learning Interests, PASA Model, Sociology